Multiculturalism, Catholicism and Us - Tester, Keith (New blackfriars, 2010)
Taylor addresses A Secular Age to an ‘us’ identified with the West. In this way the book is particularised and entered into a conversation. It is a prime example of the multiculturalism Taylor acclaims. However the paper argues that the commitment to multiculturalism forces A Secular Age to downplay the importance of Catholicism as an institution. It is contended that the book is a great work of catholicity (small ‘c’) but in need of more Catholicism (capital ‘C’).